Impact of ductal interventions on diabetes in patients with chronic pancreatitis. Issue 5 (16th October 2020) - Talukdar, Rupjyoti; Reddy, D Nageshwar; Tandan, Manu; Gupta, Rajesh; Lakhtakia, Sundeep; Ramchandani, Mohan; Kalapala, Rakesh; Basha, Jahangeer; Nabi, Zaheer; Reddy, Manohar; Darishetty, Santosh; Koppoju, Vinod; et al.
Abstract: Background and Aim: Even though ductal interventions in chronic pancreatitis (CP) are known to improve pain, its impact on diabetes is unclear. In this cohort study, we evaluated the impact of ductal interventions on diabetes in these patients. Methods: Consecutive patients with CP visiting the pancreas clinic between August 1, 2011, and July 21, 2012, were enrolled and followed until December 2018. Detailed clinical, laboratory, imaging, and treatment data were recorded at enrolment and follow‐up. Patients were followed up every 6 months through hospital visit and/or telephonic interview. Risk factors for diabetes were evaluated using logistic regression. The impact of ductal interventions on diabetes was evaluated using Kaplan–Meier survival analyses and Cox proportional hazards. Results: A total of 644 patients were enrolled of which 137 were excluded. Of these, 326 (64.3%) patients had idiopathic CP, and 283 (55.8%) patients underwent ductal intervention. The cumulative incidence of diabetes was 57.9%. Median duration between symptom onset and ductal intervention was similar irrespective of diabetes (2.6 [0.6–6.0] vs 3.0 [1.0–5.5] years; P = 0.69). Alcohol intake and pancreatic ductal calculi were independent risk factors for diabetes (odds ratio [95% confidence interval] of 2.05 (1.18–3.55), P = 0.01, and 2.05 (1.28–3.28), P = 0.003, respectively). Kaplan–Meier analyses revealed that diabetes free interval was significantly longer in patients undergoing ductal interventions, predominantly in those with idiopathic CP with obstructive ductal calculi (hazard ratio [95% confidence interval] 0.39 [0.28–0.55]; P < 0.0001). There were no differences in glycemic status in patients with non‐idiopathic CP and those with pre‐existing diabetes. Conclusion: Early ductal intervention could delay development of diabetes in patients with idiopathic CP with obstructive ductal calculi.